The north Randfontein Chinese Miners' 'Strike' of 1905 - Richardson, Peter (My University, 1975)
On the 1st April 1905, on the North Randfontein gold-mine in the Transvaal, a simmering dispute between the Chinese Indentured labourers and the mine management erupted in open violence. The whole of the Chinese work force on the mine premises was involved and mounted European police were used to quell the outbreak. As a result of this incident, described by the Conservative Colonial Secretary as a dangerous dispute over wages, fifty-three Chinese were arrested and charged with public violence and assault with intent to do harm. Following these arrests the Chinese returned to work. On the 4th April, however, they received a wage offer which formed not only the basis of the settlement at the North Randfontein, but was to serve as a model upon which the Transvaal Chamber of Mines based its wage policy towards all Chinese, for the latter's remaining period on the Rand.
African Studies Seminar series. Paper presented July 1975
Keywords: Gold miners. Recruiting. South Africa. Transvaal. History; Foreign workers, Chinese. South Africa. Transvaal. History; Gold miners. South Africa. Transvaal. History